Evaluation of automatic tools for drainage network extraction from SRTM elevation data for Paragominas Municipality, Pará, Brazil - Pereira, Jorge Luis Gavina; Ferreira, Leandro Valle; Sales, Gil Mendes; Thalês, Marcelo Cordeiro; Poccard-Chapuis, René; Rennó, Camilo Daleles; Rosim, Sérgio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Drainage extraction using elevation data represents an important step in several environmental studies. Topography is usually manipulated in Geographic Information Systems (GIS) in Digital Elevation Model (DEM) format. In the 1980s, a method was established for drainage extraction from DEM, based on depressions correction, flow direction definition, flow accumulation calculation, and drainage extraction. Elevation values can represent terrain height or tree height. DEM correction for ground height improves drainage extraction. The objective of this paper is to evaluate drainage extraction by Arc Hydro and TerraHidro hydrological tools using SRTM DEMs subjected to filtering and different forest canopy height corrections. Topographic drainage maps were used to evaluate the results. Among of drainages extracted by the Arc Hydro which presented the smallest difference in relation to the topographic maps (283 m). data were used with canopy correction 3, without filtering. TerraHidro obtained the drainage with the smallest difference in relation to topographic maps (270 m) by using filtered data with canopy correction 2